Recurrence and Familial Inheritance of Intronic NIPBL Pathogenic Variant Associated With Mild CdLS - Masciadri, Maura; Ficcadenti, Anna; Milani, Donatella; Cogliati, Francesca; Divizia, Maria Teresa; Larizza, Lidia; Russo, Silvia (Frontiers in Neurology, 2018)
Splicing mutations account for a notable fraction of NIPBL alterations underlying Cornelia de Lange syndrome but are likely underrepresented, due to overlooking of deep intronic variants by traditional and contemporary sequencing methods. We describe five subjects, belonging to three families, displaying a mild Cornelia de Lange syndrome phenotype who carry the NIPBL mutation c.5329-15A>G, affecting the IVS27 branch site, yet reported in a single case. By RNA analysis we evidenced two alternative transcripts: the exon 28 in frame skipped transcript, described in the published case and also an out-of-frame transcript retaining 14 nucleotides of IVS27 3’end. Even if both aberrant transcripts are at negligible levels, their presence justifies the CdLS phenotype shared by our patients consisting of borderline-mild cognitive impairment and slight but typical facial dysmorphisms. Transmission of the pathogenic variant from pauci symptomatic mother to her siblings emphasizes the need of molecular diagnosis also extended to deep intronic regions in patients with subtle but recognizable CdLS phenotype.